Kajian Penggunaan Sistem ‘Waste-To-Energy’ (WTE) Bagi Pengurusan Tapak Pelupusan Sisa Pembinaan - Janari, Nurul Nur Aini; Kasim, Narimah; Zainal, Rozlin; Shareh Musa, Sharifah Meryam (Research in Management of Technology and Business, 2020)
Nowadays, the construction sector in Malaysia is growing in terms of projects undertaken by the industry. However, it has led to an increase in construction waste generation. Indirectly resulting in lower levels of site management due to increased waste and limited site capacity. Therefore, the study introduces a waste-to-energy (WTE) system, a new technology that solves landfill management problems and construction waste generation. This study aims to identify the potential use of WTE systems for the management of dumping sites of construction waste and the challenges of using WTE systems for the management of dumping sites of construction waste. To achieve the objectives of the study, quantitative methods were used as primary data by conducting questionnaire distribution. The form was distributed to selected respondents, namely G7 registered contractors located around Johor. The findings of this study found that all potential uses of the system have potential in the management of construction waste disposal sites namely, potential energy, technical, system sustainability, economic, market and social. As for the challenges of using the WTE system, the challenges include shortages of energy, high costs, toxic gas emissions and the effects of global warming. It is hoped that through this study, the relevant parties will be able to apply the WTE system in the construction industry sector to improve the management of construction waste sites and reduce the generation of construction waste in Malaysia.